(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the scientific-theoretical views of a number of linguists on words and phrases have been studied, the features of words and phrases in linguistics have been deeply researched, and similar and their differences, their functions in the sentence and outside the sentence, their specific aspects are studied, as well as the differences of the phrase from the word, compound word, sentence and phrase are also discussed .